Design, synthesis, antimicrobial and antifungal activities of new 1,2,4-triazole derivatives containing 1H-tetrazole moiety - Frolova, Y.; Kaplaushenko, A.; Nagornaya, N.; Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович; Нагорна, Наталія Олександрівна (My University, 2020)
Objective: Antimicrobials and antifungals are the most acquired drugs in the world. Today, it becomes necessary to create new drugs with antimicrobial and antifungal effect. The purpose of our research is the synthesis of new series of 5-(1Н-tetrazole-1-yl)-4H-1,2,4-triazole-3-amine, the establishment of physicalchemical, antimicrobial and antifungal properties for all synthesized compounds. Material and Method: 5-(1Н-tetrazole-1-yl-methyl)-4H-1,2,4-triazole-3-yl-1-(alkyl-, aryl-)-methanimines were synthesized by reacting of 5-(1H-tetrazole-1-yl-methyl)-4H-1,2,4-triazole-3-amine with aldehydes in acetic acid. Then, sodium borohydride was selected as a reducing agent, which allowed for the restoration of the double bond. The structures of synthesized compounds were confirmed by IR, 1H NMR and mass spectra. The synthesized compounds were evaluated for antimicrobial and antifungal activity by "serial dilutions" method. Result and Discussion: During the synthetic studies the new series of 22 compounds were obtained. The 5- (1Н-tetrazole-1-yl-methyl)-4H-1,2,4-triazole-3-yl-1-(5-nitrofuran-2-yl)methanimine was observed to be most possessing good antimicrobial and antifungal activity and has exceeded the reference standard for Staphylococcus aureus (12,5/25 mg/ml), Escherichia coli (50/100 mg/ml), Pseudomonas Aeruginosa (100/200 mg/ml), Candida albicans (50/50 mg/ml).
Keywords: 1,2,4-triazole; 1Н-tetrazole; antimicrobial and antifungal activity